POTENTIAL BIAS IN THE ISOLATION OF PYRIDINIC NITROGEN FRACTIONS FROM CRUDE OILS AND ROCK EXTRACTS USING ACID EXTRACTION AND LIQUID CHROMATOGRAPHY - Li M.; Larter S.R. (My University, 2001)
Simple mineral acid extraction and open column chromatographic methods commonly used to isolate pyridinic nitrogen fractions from crude oil and rock extract appear to yield severely altered distributions of alkylquinolines and benzoquinolines. This potential analytical bias, if not recognized, could lead to incorrect geochemical interpretations.
Keywords: ORGANIC NITROGEN COMPOUNDS; FRACTIONATION TECHNIQUES; POLAR COMPOUNDS; MOLECULAR MIGRATION INDICATORS